Exotica in a world of temptation, obsession is the deadliest desire - Danna, Mychael 1958- (Buena Vista Home Entertainment, 1999)
An erotic table dancer at a strip club has sex with two mysterious, obessive strangers and gets involved in a deadly plot.
1.66:1 aspect ratio
Orig.: Kanada, USA 1994
Keywords: Feature films; Films for the hearing impaired; Videos (DVD)